What is affect? (Journal of Philosophy Culture and Political Science, 2023)
In this article, the relationship between affect and becoming in Deleuze and Guattari's philosophy is explored. It is argued that affects and becoming are closely linked, and where there is becoming, there is also affect. Conversely, the absence of becoming implies the absence of affect. The concept of becoming is described as a process of desubjectification, where the ego loses its boundaries and transforms into the unbounded entity known as the schizo. Various identities or names can be assumed by the schizo, each representing a zone of intensity that the schizo moves through and derives value from. These identities should not be interpreted as permanent identifications in the psychoanalytic sense, but instead as temporary markers that the schizo transitions through like a nomad. The fact that the schizo's state of being is pathological is emphasized, and it requires a novel analytical approach called schizoanalysis, which aims to comprehend the specific logic of becoming that defines the schizo experience. Overall, crucial concepts in Deleuze and Guattari's philosophy, such as the correlation between affect and becoming and the significance of desubjectification in understanding the schizo experience, are introduced in this article. It also highlights the importance of innovative analytical approaches that consider the fluid and boundless nature of the schizo's identity.Key words: Deleuze, Guattari, affect, desubjectification, schizoanalysis, identity